Theory of optical dispersive shock waves in photorefractive media - El, G. A.; Gammal, A.; Khamis, E. G.; Kraenkel, Roberto André [UNESP]; Kamchatnov, A. M. (Amer Physical Soc, 2007)
The theory of optical dispersive shocks generated in the propagation of light beams through photorefractive media is developed. A full one-dimensional analytical theory based on the Whitham modulation approach is given for the simplest case of a sharp steplike initial discontinuity in a beam with one-dimensional striplike geometry. This approach is confirmed by numerical simulations, which are extended also to beams with cylindrical symmetry. The theory explains recent experiments where such dispersive shock waves have been observed.